Analisis Makna Dan Pesan Pada Sampul Majalah Mingguan Tempo Dengan Kajian Segitiga Makna - Adiyatma Nur Hidayat; Fikri Hakim (Pusat Riset dan Inovasi Nasional, 2023)
This research examines the symbols on the cover of the October 2022 edition of the weekly magazine Tempo. This research aims to describe the symbols on the cover of the October 2022 exclusive edition of Tempo magazine. This research uses a qualitative descriptive method approach using data collection techniques. data namely observation and documentation. The results of this study indicate that there are two language symbols on the cover of the October 2022 edition of weekly magazine Tempo, namely verbal language symbols (in the form of words and sentences written in Indonesian) and non-verbal in the form of pictures and graphic illustrations showing the contents of the news in the magazine. Data analysis uses the theory of semantic triangles made by Richad and Ogden which refers to symbol, reference, referent